Investigating Gender Differences in the Attitude and Achievement of Secondary School Students Towards Stem Education in Plateau State - Dawal, B. S. (Kashere Journal of Education, 2021)
The study investigated gender differences in the attitude and achievement of secondary school students towards STEM education in Plateau. The descriptive survey design was used to obtain information on the attitude of students towards science and ex-post facto design was used to obtain achievement scores of the students in science subjects. Out of the population of 391 schools, a sample of 298 senior secondary school students consisting 178 males and 120 females from 6 secondary schools in Plateau state were used. Two schools were selected from each of the three senatorial zones. The two instruments which are Attitude Towards Science Questionnaire (ATSQ) a five point Likert Scale and Students Achievements Scores (SAS) in science subjects were validated by experts. The reliability index of r= 0.83 and r=0.87 of the instruments were obtained respectively using Cronbach’s Coefficient Alpha. Two research questions were answered using descriptive statistics of mean and standard deviation and two hypotheses were tested using t-test at 0.05 level of significance. The results of the study revealed significant differences in the attitude of male and female students in favour of the males. The study also revealed that the achievement scores of male students in science were higher than their female counterparts. It is thus recommended among others that maximum efforts should be made by teachers to improve students’ attitude towards STEM education.